Pemanfaatan Minyak Jelantah Menjadi Biodiesel Dengan Katalis ZnO Presipitan Zinc Karbonat : Pengaruh Waktu Reaksi Dan Jumlah Katalis - Hamsyah Adhari; Yusnimar Yusnimar; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is a highly potential material to replace diesel fuel. Renewable and environmentally friendly. Waste cooking oil can be used as raw material for making biodiesel. Free fatty acid levels are high in waste cooking oil requiring pretreatment (esterification) in the process of making biodiesel. In this study transesterification reaction conducted by catalyst synthesized ZnO of ZnCO3. This study aims to determine the effect of variations in reaction time and variations the amount of catalyst to yield biodiesel produced. After esterification of free fatty acid levels in the oil can be lowered from 6.09% to 1.02%. The transesterification reaction was held at temperatures 65oC; The mole ratio of oil and methanol is 1:18; ZnO catalyst amount is 0,5%, 0,6% and 0,7%; reaction time is 50, 75, and 100 minutes. The highest biodiesel yield obtained was 94.31% on the amount of catalyst 0.7% w / w of cooking oil with a reaction time of 100 minutes. Characteristics of biodiesel produced, namely: density and viscosity at a temperature of 40°C is 866,50 kg/m3 and 5,74 mm2/s, The flash point is 190oC, acid value 0,60 mg-KOH/g-biodiesel and the content of alkyl ester 98,42%.Keywords: Biodiesel, Waste Cooking Oil, Esterification, Transesterification, ZnO